2016
DOI: 10.1177/0897190016637793
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating a Drug Information Consult into a Pharmacy Practice Course to Build Literature Search and Evaluation Skills Through a 3-Stage Model

Abstract: The 3sDIC, although not a substitute for a complete drug information course, demonstrated a streamlined approach for Pharmacy year 2 (P2) students to acquire and develop drug information skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…18 Additionally, students appreciate assignments in which realistic clinical questions are used and they develop answers using an EBM framework. 19,20 Although the EBM curriculum had been streamlined, it yielded results similar to the former curriculum in terms of pharmacy student learning. 7 The first learning component that was adjusted was five hours of librarianfacilitated content in the P2 year, which consisted of learning literature acquisition skills and completing a written assignment (ie, a mini-clinical inquiry assignment).…”
Section: Discussionmentioning
confidence: 99%
“…18 Additionally, students appreciate assignments in which realistic clinical questions are used and they develop answers using an EBM framework. 19,20 Although the EBM curriculum had been streamlined, it yielded results similar to the former curriculum in terms of pharmacy student learning. 7 The first learning component that was adjusted was five hours of librarianfacilitated content in the P2 year, which consisted of learning literature acquisition skills and completing a written assignment (ie, a mini-clinical inquiry assignment).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the benefits of reinforcing DI competencies to facilitate student retention of core DI skills, increase confidence, and understand its routine real‐world applications 13–16 . In addition, DI skills may be incorporated into simulations and EBM topics, as well as incorporated into longitudinal courses 11,12,17–19 .…”
Section: Education and Trainingmentioning
confidence: 99%
“…9,10 Studies have shown the benefits of reinforcing DI competencies to facilitate student retention of core DI skills, increase confidence, and understand its routine real-world applications. [13][14][15][16] In addition, DI skills may be incorporated into simulations and EBM topics, as well as incorporated into longitudinal courses. 11,12,[17][18][19] Intentional incorporation of literature evaluation skills as an APPE-readiness assessment has been used to ensure students demonstrate mastery prior to entering APPEs.…”
Section: Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[9][10][11] Particularly in Japan where EBM skills are In contrast, in the US school surveyed, where EBM training and presentations are required throughout the didactic courses and experiential education, all environmental barriers were identified by <50% of American students, yet EBM use is still suboptimal. Although several studies showed the effectiveness of EBM training in increasing knowledge in students and practitioners with various methods, including a brief one day workshop, journal club, monograph assignment, and computer-or lecture-based instructions, [29][30][31][32][33][34] knowledge of EBM does not equate to their actual usage of EBM. Some studies have shown no changes in clinician behavior to use EBM even though training improved their knowledge and skills.…”
Section: -24mentioning
confidence: 99%